Advancing Food Sustainability: A Prototype Platform for Informed Decision-Making - Vasquez-Perez, O; Contreras-Arredondo, R; Espinoza-Perez, A; Espinoza-Perez, L; Velastin-Osorio, N (SPRINGER INTERNATIONAL PUBLISHING AG, 2025)
Transforming our food system into one that is more sustainable and equitable emerges as a critical requirement for a future in which humanity thrives in harmony with the environment. In this context, massive food services emerge as pivotal actors where small changes can lead to significant impacts. Furthermore, considering that nutrition labels and eco-labels can support consumers in making healthier and more sustainable choices, tools are needed to access this information framed in their territorial reality. In this context, our study introduces the development of a prototype platform customized for a specific massive food service in Chile. This platform facilitates menu assessment and design by providing insights into various environmental impacts and nutritional aspects, empowering informed decision-making.